Factors Affecting Customers' Preferences for Nepalese Coffee in Kathmandu Valley: A Poisson Regression Analysis of Count Data - Basnet, Sunil; Devkota, Niranjan; Mahapatra, Sushanta; Upretee, Sahadeb (Quest Journal of Management and Social Sciences, 2024)
Background: Approximately 65 percent of Nepalese coffee is exported, while the remainder is processed and sold domestically. Nepalese coffee, recognized for its organic cultivation from high altitudes, is witnessing a shift in consumer preference from tea to coffee in Nepal. Despite this shift, the market for Nepalese coffee remains underdeveloped in the Kathmandu Valley. Objective: This study aims to examine the factors affecting consumers' preferences for Nepalese coffee in the Kathmandu Valley. It seeks to identify the barriers to increasing domestic consumption and explore potential strategies to enhance the market for Nepalese coffee. Method: An explanatory research design was employed, utilizing a structured questionnaire and convenience sampling to collect data from 403 coffee consumers in the Kathmandu Valley. The data was analyzed using Poisson regression to assess the factors influencing coffee consumption patterns and preferences. Result: The study revealed that 99.06 percent of respondents consume coffee, but only 5.66 percent prefer Nepalese coffee. However, 32.78 percent of respondents expressed a strong interest in drinking Nepalese coffee. Key barriers identified include the perceived quality of Nepalese coffee, insufficient promotion, and unfavorable government policies. The analysis indicates that improving advertising, enhancing coffee quality, and increasing promotional efforts could significantly boost domestic consumption. Conclusion: To develop the market for Nepalese coffee, coffee businesses should focus on investing in production, marketing, and promotional activities. Additionally, government incentives and subsidies for coffee entrepreneurs could facilitate growth. Effective advertising and promotion, combined with quality improvements, are essential for expanding the Nepalese coffee market and increasing consumer preference. Paper Types: Research Paper Keywords: Coffee, Nepalese Coffee, Costumers, Costumers’ preferences, Kathmandu valley